Interdependence between China and Japan economy : the effects of the Senkaku/Diaoyu conflict. - Chen, Zhou. (2013)
Large scale boycott against Japanese products broke out in China after Japanese government purchased the Senkaku/Diaoyu islands, leading to a significant decrease in the sales of Japanese products in China. To measure the effects of the island dispute on Sino-Japan trade, a gravity model is employed. In addition, Sino-Japan trade pattern after the boycott is compared with Sino-Germany, Sino-US and Sino-Korea trade pattern. Comparisons show that Sino-Japan trade is negatively affected by the boycott. Additionally, an industry level analysis of Sino-Japan trade indicates that the ‘highly visible’ motor vehicle industry is most seriously affected while the ‘relatively invisible’ machinery and electronic industry is barely affected.